Phylogenetic Study of Bufonidae (Amphibia: Anura) From West Sumatra (Indo-nesia) Based on Cytochrome bGene - Djong Hon Tjong; Dewi Imelda Roesma; Silvia Indra (Journal of Tropical Life Science, 2021)
Bufonidaeis a widelydistributedamphibian family around the world, includingIndonesia (Sumatra) and Asia. Sumatra is an island thathas separated because of sea level increaseand createsa gene flow barrier for amphibiansin Sumatra and Asia. This research aims to analyze Bufonidae phylogenetic, which existsin sev-erallocations in West Sumatra and Asia based on gene cytochromeb analysis. Samples were collected from six localities in West Sumatra. DNA extraction and amplification havebeen done in Genetics and Cell BiologyLaboratory, Andalas University, whereas DNA sequencing wasanalyzed at MacroGen USA DNA Se-quencing Laboratory, South Korea. About 14 tissue samples of Bufonidae from West Sumatra havebeen analyzed. The relationship of Bufonidae phylogeneticsin Sumatra and Asia wasdivided into three main clusters.The first cluster consistsof Duttaphrynus melanostictus, Duttaphrynus himalayanus, Bufo japonicus and Ingerophrynus quadriporcatus. The second cluster consists ofLeptophryne bar-bonica, Phrynoidis juxtasperand Phrynoidis aspera. The third cluster only con-sists of Ansoniasp. D.melanostictus in Sumatra is closer to D.melanostictus from India with 0.3-0.5% sequence divergence and it is a group of paraphyletic with D.melanostictus from Vietnam, Taiwan, and China. L.barbonicafrom Padang Pan-jang with Bengkulu possibility different species (sequence divergent 26.1%). P.aspera(Solok&Sijunjung) with (Malampah 1-2, Rimbopanti, Palupuh Agam) indicated genetic differences between populations(sequence divergence1.9%-2.2%). For Ansonia sp. and I.quadriporcatusneed further analysis to determine the relationship phylogenetically